Phenotypic variability, race profiling and molecular diversity analysis of Indian populations of Fusarium oxysporum f. sp. lentis causing lentil wilt - Dubey, Sunil Chandra; Sharma, Vaishali Datt; Kumar Prajapati, Vinod; Akhtar, Jameel; Kandan, Aravindaram (Folia microbiologica, 2022)
Wilt (Fusarium oxysporum f. sp. lentis; Fol) is one of the major diseases of lentil worldwide. Two hundred and thirty-five isolates of the pathogen collected from 8 states of India showed substantial variations in morphological characters such as colony texture and pattern, pigmentation and growth rate. The isolates were grouped as slow (47 isolates), medium (118 isolates) and fast (70 isolates) growing. The macroconidia and microconidia (3.0-77.5 × 1.3-8.8 μm for macroconidia and 1.8-22.5 × 0.8-8.0 μm for microconidia for length × width) were variable in size and considering the morphological features, the populations were grouped into 12 categories. Seventy representative isolates based on their morphological variability and place of origin were selected for further study. A set of 10 differential genotypes was identified for virulence analysis and based on virulence patterns on these 10 genotypes, 70 Fol isolates were grouped into 7 races. Random amplified polymorphic DNA (RAPD), universal rice primers (URPs), inter simple sequence repeats (ISSR) and sequence-related amplified polymorphism (SRAP) were used for genetic diversity analysis. URPs, ISSR and SRAP markers gave 100% polymorphism while RAPD gave 98.9% polymorphism. The isolates were grouped into seven clusters at genetic similarities ranging from 21 to 80% using unweighted paired group method with arithmetic average analysis. The major clusters include the populations from northern and central regions of India in distinct groups. All these three markers proved suitable for diversity analysis, but their combined use was better to resolve the area specific grouping of the isolates. The sequences of rDNA ITS and TEF-1α genes of the representative isolates were analysed. Phylogenetic analysis of ITS region grouped the isolates into two major clades representing various races. In TEF-1α analysis, the isolates were grouped into two major clades with 28 isolates into one clade and 4 remaining isolates in another clade. The molecular groups partially correspond to the lentil growing regions of the isolates and races of the pathogen.
Keywords: genetická variace; nemoci rostlin; Lens Plant; DNA primery; Phylogeny; Random Amplified Polymorphic DNA Technique; technika náhodné amplifikace polymorfní DNA; ribozomální DNA; Plant Diseases; Biological Variation, Population; DNA, Ribosomal; čočka; Genetic Variation; DNA Primers; Fusarium; Cicer; biologická variabilita populace; fylogeneze